The Influence of the Contextual Teaching and Learning Approach on Elementary School Students' Conceptual Understanding Ability in Mathematics Learning - Rambe, Rika Putri (Jurnal Pendidikan Profesi Guru, 2026)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) approach on elementary school students' mathematical conceptual understanding. The problem of low conceptual understanding remains a challenge in mathematics learning, especially when students are unable to connect the material to real contexts. This study used a quasi-experimental method with a pretest-posttest control group design. The research subjects were 56 fifth-grade students who were divided into an experimental group that received CTL learning and a control group that followed conventional learning. The instruments used were a conceptual understanding test based on conceptual understanding indicators and an observation sheet for the implementation of learning. The results showed that there was a significant increase in the conceptual understanding ability of students who learned using the CTL approach. The average posttest score of the experimental group reached 82.4 compared to the control group of 71.6, with a gain score of 0.61 for the experimental group and 0.42 for the control group. These data indicate that CTL learning is more effective in promoting conceptual understanding through activities that connect material to real experiences. The implications of this study indicate that teachers need to integrate authentic contexts in mathematics learning to strengthen students' conceptual construction meaningfully.